Intrapleural fibrinolytic therapy for pleural infections: Outcomes from a cohort study - Glenn Khai Wern Yong; Jonathan Jia Jun Wong; Xiaoe Zhang; Carmen Pei Sze Tan; Xiao Na Wang; Poh Seo Quek; Kim Hoong Yap (Annals, Academy of Medicine, Singapore)
Introduction: Pleural infections are a significant cause of mortality. Intrapleural fibrinolytic therapy (IPFT) utilising alteplase and dornase is a treatment option for patients unsuitable for surgery. The optimal dose of alteplase is unknown, and factors affecting treatment success in an Asian population are unclear. We sought to determine the factors affecting treatment success in Tan Tock Seng Hospital, Singapore and evaluate the efficacy of lower doses of IPFT. Method: A retrospective analysis of patients with pleural infections treated with IPFT between July 2016 and November 2023 was performed. Treatment success was defined as survival without surgery at 3 months. Data, including patient demographics; comorbidities; RAPID (renal, age, purulence, infection source and dietary factor) scores; and radiological characteristics, were extracted from medical records and analysed. Linear mixed effects model and logistic regression were performed to determine factors affecting treatment success. Results: A total of 131 cases were analysed. Of these, 51 (38.9%) reported positive pleural fluid culture, and the most common organism was Streptoccocus anginosus. Mean age was 65 years (standard deviation [SD] 15.5). Mean time from chest tube insertion to first dose of IPFT was 10.2 days (SD 11.5). Median starting dose of alteplase was 5 mg. Treatment success was reported in 112 cases (85.5%). There were no significant differences between the alteplase dose and radiological clearance. Patient age (odds ratio [OR] 0.94, confidence interval [CI] 0.89–0.98) and interval between chest tube insertion to first dose (OR 0.95, CI 0.91–0.99) were statistically significant variables for the treatment success. Conclusion: Lower starting doses of alteplase remain effective in the treatment of pleural infection. Early IPFT may result in better outcomes.